Straw mulch improves soil carbon and nitrogen cycle by mediating microbial community structure and function in the maize field - Liu, Bangyan; Dai, Yisha; Cheng, Xin; He, Xian; Bei, Qicheng; Wang, Yifan; Zhou, Yuling; Zhu, Bo; Zhang, Kangping; Tian, Xiaoqin; Duan, Meichun; Xie, Xiaoyu; et al. (Frontiers in Microbiology, 2023)
This study was conducted to investigate the capability of the microbial community characteristic and soil variables to promote carbon and nitrogen cycles in maize fields under straw mulch. We covered the surface soil of the maize field with different amounts of wheat straw (0 kg/ha, 2250 kg/ha, and 4500 kg/ha), used 16S rRNA and ITS sequencing, Biology ECO-plate, traditional enzymology, TOC analyzer, and HPLC to measure bacterial and fungal community composition and functions, characteristics of microbial carbon source metabolism, carbon and nitrogen fraction, enzyme activity, and organic acid content in the maize rhizosphere and non-rhizosphere. Results indicated that short-term straw mulch insignificant effected on the alpha diversity of bacterial and fungal communities, whereas significantly influenced their beta diversity. The results of functional prediction revealed that straw mulch considerably boosted the relative abundances of bacteria belonging to chemoheterotrophy, aerobic chemoheterotrophy, ureolysis, and nitrogen fixation while inhibited fermentation and nitrate reduction in maize rhizosphere soil. These processes primarily drove the C and N cycles in soil. Straw mulch also improved fungal saprotrophs by raising the proportion of Chaetomiaceae and Chaetosphaeriaceae. The Biology ECO-plate results illustrated that straw mulch weakened the metabolism capacity of microbial labile carbon resources. As a result, the labile C and N fractions were raised under straw mulch. Our results also showed that straw mulch primarily regulated the microbial community structure in rhizosphere soil by significantly decreasing Firmicutes and Ascomycota relative abundance, while incerasing Basidiomycota. The fungal community structure is more than bacterial for affecting soil microbial biomass carbon, readily oxidizable organic carbon, dissolved organic carbon, available nitrogen, ammonium, and nitrate directly and indirectly through malic acid content and cellulase, protease, and amylase activity. Overall, our findings imply that straw mulch might influence the bacterial and fungal community structures, thereby boosting the production of labile C and N components and accelerating the C and N cycle in maize fields.